Gibanje teologije osvoboditve - Jurekovič, Igor (Poligrafi, 2020)
The formation of the latin American liberation theology as a movement begun in the 50s and gradually gained momentum up to its peak in the early 70s of the 20th century. In accordance with Pierre Bourdieu's sociology, the article claims that the formation of the movement was aided by objective, structural social conditions as well as the corresponding perception of social actors. The key social conditions that the article focuses on are latin American industrialization, an institutional crisis in the Roman Catholic Church in latin America, the Second Vatican Council, an emerging intellectual independence of the continent and the formation of well-educated theologians of liberation. The blossoming of the movement was followed by an internal then a Vatican conservative restoration, which managed to curtail the movement in ten years' time. in light of the concluding discussion of liberation theology's downfall, the article suggests further research on penteco-stalism, which has grown in popularity in the last forty years, coinciding with the implementation of neoliberal structural reforms in the Global South.
Keywords: družbeni sistem; Latinska Amerika; relacijska sociologija; religijska gibanja; Rimskokatoliška cerkev; socialne razmere; teologija osvoboditve